Investigating the role of analogies as tools for teaching topics in modern physics - I. Rosner, Heike (Improving University Science Teaching and Learning, 2023)
Metaphors and analogies play a very important role in human thinking and perception (Lakoff & Nu´nez; 2000) and we use them frequently when try˜ing to understand or explain complex concepts (Bjerregaard et al.; 1995). Hence, analogies to classical physics are often the method of choice in didactic approaches to teach modern physics. However, many of these models describe certain aspects of a phenomenon very well, but do no longer apply when describing the more complicated contexts of the phenomenon. Inconveniently, these models or analogies are very difficult to erase or substitute because of their apparent inbuilt logic and simplicity. Here, the aim was to investigate the role of such models and analogies when studying the basics of NMR spectroscopy. Thereby, it was also explored whether alternative strategies to use models and analogies could be developed.